Hypothermia in Preterm Neonates in Oman: A Retrospective Study - Mohamed Abdellatif; Fatma Musallam Al Ghafri; Murtadha Al Kahbori; Ashfaq Ahmad Khan; Nihal Al Riyami; Moataz Hassan (Oman Medical Journal)
Objectives: To determine the prevalence of hypothermia among preterm infants born before 32 weeks of gestation and whether their temperature at admission is associated with neonatal and maternal risk factors and gestational age. Furthermore, the study evaluates the association between admission temperature, neonatal morbidity, and in-hospital mortality. Methods: This study involved an eight-year retrospective analysis of preterm neonates born < 32 weeks of gestation and admitted to the neonatal intensive care unit at a tertiary hospital in Oman, from 2010 to 2017. Results: The study included 587 preterm infants with a mean gestational age of 28.4 weeks, a mean birth weight of 1154.2 g, and a mean admission temperature of 35.5 °C. Hypothermia (axillary temperature < 36.5 °C) was present in 509 (86.7%) infants. In univariate analysis, only birth weight and neonatal resuscitation were associated with admission temperature (< 36.5 °C). In the multivariate analysis, only intraventricular hemorrhage demonstrated a significant association with the incidence of hypothermia. Conclusions: Most preterm newborns had hypothermia upon admission to the neonatal intensive care unit, which is associated with essential morbidities. More aggressive interventions are warranted to reduce the incidence of hypothermia in preterm infants.